A review of biodegradable biliary stents made of magnesium metals: Current progress and future trends - Ling Liu; Tuo En Liu; Tan To Cheung (Journal of Magnesium and Alloys)
Biliary system, which is responsible for transporting bile from the liver into the intestine, is commonly damaged by inflammation or tumors eventually causing liver failure or death. The implantation of biliary stents can effectively alleviate both benign and malignant biliary strictures, but the plastic and metal stents that are currently used cannot degrade and nearly has no beneficial biological effects, therefore their long-term service can result into inflammation, the formation of sludges and re-obstruction of bile duct. In recent years, magnesium (Mg) metal has been received increasing attention in the field of biomedical application due to its excellent biocompatibility, adequate mechanical properties, biodegradability and other advantages, such as anti-inflammatory and anti-tumor properties. The research on biliary stents made of magnesium metals (BSMM) has also made significant progress and a series of experiments in vitro and vivo has proved their possibility. However, there are still some problems holding back BSMM's clinical use, including rapid corrosion rate and potential harmful reaction. In this review, we would summarize the current research of BSMM, evaluate their clinical benefits, find the choke points, and discuss the solving method.